Effects of hormonal regulation on cell number and cell size in determining fruit size: a mini-review - Siti Khadijah A. Karim; Zamri Zainal; Nik Marzuki Sidik (Penerbit Universiti Kebangsaan Malaysia, 2024)
Fruits are sold by weight, and hence, fruit size is a central indicator of fruit yield and quality. In horticultural industries, fruit growers and researchers continually search for and improve cultivation methods to enhance fruit size. By providing a fundamental understanding of how fruit size is regulated in plants, the process of cell number production followed by the increase of cell size has been widely studied. Molecular and cellular approaches provide direction to both scientists and breeders in fruit quality enhancement. This mini-review discussed the interplay among major plant hormones in regulating cell number production and cell size in horticultural plants. We focused on hormones that are mainly involved in determining cell proliferation and cell size and on their interaction during genetic regulation and their signaling pathways, which in turn, influence final fruit size. We also deliberated the current findings around this research niche at cellular and molecular levels. This will ultimately assist breeders in improving the fruit quality, and yield and increase profit.